O lugar de ser criança: percepções da infância a partir das narrativas dos pais no município de Tefé- Am - Lira, Naraiza Caldas (2020)
This dissertation is the result of reflections and research carried out with children and their families in a neighborhood in the city of Tefé, in the State of Amazonas, called Nossa Senhora de Fátima, but also known as Vila Neck. Our research shows how children live their childhood in this place. To this end, we have deepened our study from two main contexts, that is, the family and the neighborhood. Did you seek to know how the children of Nossa Senhora de Fátima see their social space, their childhood and their place? Our main objective is to understand how children and their parents conceive of social space and childhood in the neighborhood of Nossa Senhora de Fátima. And we started from it for the specific objectives that had the purpose of knowing the neighborhood from its residents; as well as identifying how children and their parents understand childhood in the neighborhood; and finally to understand the family contexts in which children are inserted. We adopted an interdisciplinary perspective, with the theoretical participation of sociology, history and anthropology. We chose the Social Case Study methodology, a research method highlighted by Becker (1997). We had three important moments of data collection, exploratory research, socioeconomic diagnosis, and the social case study with two families. The work is organized into three main chapters: "The methodological paths that lead to the place of being a child"; "Children and Childhood in the Context of Human Sciences" and the last one, "Being a Child: Perceptions of Childhood from the subjects' voices".